2001
DOI: 10.1103/physrevb.64.134525
|View full text |Cite
|
Sign up to set email alerts
|

Glassy slowing of stripe modulation in(La,Eu,Nd)2

Abstract: 63 Cu and 139 La nuclear quadrupole resonance and Zeeman perturbed nuclear magnetic resonance experiments are performed on the striped phase of the high temperature superconductors La2−xBaxCuO4 and La2−x−y(Nd,Eu)ySrxCuO4. The first goal of the present study is to utilize the fact that ordered Cu magnetic moments exert a static hyperfine field on the 63 Cu and 139 La nucleii to deduce the charge density and ordered moment within the CuO2 planes. A hyperfine broadened NQR lineshape is observed in both La2−xBaxCu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
116
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 111 publications
(353 reference statements)
17
116
0
1
Order By: Relevance
“…12 is the ac susceptibility of La 1−δ MnO 3 sample. The frequency dependence of the real and imaginary part of the susceptibility as well as their absolute values are indicative of the cluster glass behaviour similarly as reported by Ghivelder et al The situation may be similar to that observed in the lanthanum cuprates, where slowing down of the spin and/or charge fluctuations results in a strong peak in the spinlattice relaxation for the La nuclei and in a loss of signal on the Cu nuclei and it is ascribed to the glassy magnetic state [23][24][25]. It is interesting that for both Cu and La signals stretched exponential like spin-echo decay is observed in the slow fluctuation limit similarly to the one for FMI signals in manganites, while in the motionally narrowed limit, below a transition temperature T charge , corresponding to the localization of charge-ordered stripes, a Lorentzian single-exponential spin-echo decay is detected [24,26,27].…”
Section: Resultssupporting
confidence: 79%
“…12 is the ac susceptibility of La 1−δ MnO 3 sample. The frequency dependence of the real and imaginary part of the susceptibility as well as their absolute values are indicative of the cluster glass behaviour similarly as reported by Ghivelder et al The situation may be similar to that observed in the lanthanum cuprates, where slowing down of the spin and/or charge fluctuations results in a strong peak in the spinlattice relaxation for the La nuclei and in a loss of signal on the Cu nuclei and it is ascribed to the glassy magnetic state [23][24][25]. It is interesting that for both Cu and La signals stretched exponential like spin-echo decay is observed in the slow fluctuation limit similarly to the one for FMI signals in manganites, while in the motionally narrowed limit, below a transition temperature T charge , corresponding to the localization of charge-ordered stripes, a Lorentzian single-exponential spin-echo decay is detected [24,26,27].…”
Section: Resultssupporting
confidence: 79%
“…23 Na spectra broaden substantially at the same temperature range where ac susceptibility data show a broad maximum [4]. Such a spectrum proves a quasi-static and spatially disordered field distribution in NaCaCo 2 F 7 .…”
Section: Nmrmentioning
confidence: 75%
“…23 Na NMR spectra Figure 2(a,b) shows the angle dependent, with respect to the external magnetic field, 23 Na NMR field-sweep spectra from [1 1 1] to [1 0 0] direction at 80 K and at representative temperatures for [1 0 0] direction, respectively. The spectra can be described by diagonalizing the full NMR static Hamiltonian.…”
Section: Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason NMR and neutron scattering detect different onset temperatures of the SDW is that each experimental probe has a different characteristic measurement time scale [28,29]. Elastic neutron scattering measurements would consider the SDW 'static' when fluctuations slow down to below the instrument resolution of ∼ 1meV.…”
mentioning
confidence: 99%